Pengaruh Tingkat Pendidikan, Skala Usaha, Umur Usaha, dan Pengetahuan Akuntansi Terhadap Penggunaan Informasi Akuntansi - Gustarinda, Evi; Adi, Suyatmin Waskito (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This study aims to determine the influence of education level, business scale, business age, and accounting knowledge on the use of accounting information in micro, small, and medium enterprises (MSMEs) in Surakarta City. Data collection techniques used questionnaires with purposive sampling method. The type of data used is primary data with a sample of 104 MSME owners in Surakarta. Data analysis methods include descriptive analysis, multiple linear regression analysis, t-test, f-test, and determination coefficient test using SPSS 25. The research results show that education level and accounting knowledge have a significant effect on the use of accounting information in MSMEs. The variables of business scale and business age have no significant effect on the use of accounting information in MSMEs in Surakarta.